Bio-camera and bio-screen: inclusive use of smartphone in the context of performer training. Issue 2 (3rd May 2020) - Makrzanowska, Anna
ABSTRACT: The first part of the article introduces the concept of bio-camera and bio-screen seen as a staged synergy between the performer's living body and the accessible transmedia object: a smartphone. The point of departure for the investigation of the performative potential of the digital objects comes from Kantor's conception of the 'bio-object' – where performer and object have the same degree of agency and both are treated as dramaturgical material or an artwork. In order to discuss the ontological status of bio-screen and bio-camera the argument investigates the Theatre Cricot2's bio-object and examines an everyday immanent synergy between a living body and a smartphone. The function of multiple/multidirectional types of immanent synergies are explained and differentiated from the staged synergy that is activated in the context of performance. The second part of this article offers a detailed evaluation of a set of exercises with smartphones that entail the use of the telematic connection. Given that the bio-screen and bio-camera represent a broad range of approaches, this article narrows its focus to a chosen set of exercises presented in the form of a semi-photo essay together with analytical commentary. Therefore, the first and second parts differ in the manner of presentation and articulation.